70 Years of Ibirapuera Park: Assessment of Ecosystem Services Provided by the Creation of Urban Spaces in Recovered Mining Areas - Casali-Rossi, Maria Flávia; Silva Neto, Wilson Levy Braga da; Gallego, Jorge L. (Technical and Scientific Journal Green Cities, 2025)
Objective - The objective of this research was to analyze the success of the implementation of Parque Ibirapuera as an alternative for the recovery of a mined area by evaluating the provision of Ecosystem Services at the site.Methodology - The research conducted from July to December 2024 adopted a qualitative bibliographic approach, with a descriptive and exploratory focus based on the Bardin method (2016).Originality/Relevance - The originality of the research lies in the absence of scientific articles correlating the themes of urban resilience, smart and sustainable cities, and the recovery of mined areas.Results - The results demonstrate that Parque Ibirapuera, 70 years after its inauguration, continues to be one of the most important centers and providers of Ecosystem Services in the municipality of São Paulo/SP.Theoretical/Methodological Contributions - Due to the unavailability of historical data, the study brings theoretical contributions in the area of urban planning on the topic, given the scarcity of scientific research on the subject.Social and Environmental Contributions - The validation that exhausted mining areas can be transformed into parks, these spaces being good alternatives for urban replanning after the consolidation of cities. These parks, by promoting Ecosystem Services, reflect urban resilience in smart and sustainable cities.
Keywords: Smart and Sustainable Cities; Urban Resilience; Urban Space; Mining Restoration